Implementing Deuteronomy 6:6–9 as a Learning Method in Christian Education: A Qualitative Study on Student Behavior - Budianto, Johanes MJ (LP. Ma'arif Janggan Magetan, 2024)
This study examines the implementation of learning methods based on Deuteronomy 6:6–9 within the Christian Education Curriculum at Hope for the Nation Christian Junior High School, Cilincing, North Jakarta, particularly in addressing students’ behavioral issues. Using a qualitative descriptive approach, the research emphasizes in-depth analysis to understand meaning and implementation processes in real educational contexts. Data were collected through classroom observations and semi-structured interviews involving Christian religious education teachers and students. The collected data were analyzed through systematic organization, coding, identification of patterns and themes, and interpretative analysis aligned with the research objectives. The findings indicate that Deuteronomy 6:6–9–based learning methods are consistently implemented through repetitive teaching, direct instruction, discussion, and the use of written and visual learning media. These methods contribute to observable improvements in student behavior, including increased discipline, greater respect toward teachers and peers, higher participation in learning activities, and improved responsibility within the school environment. However, the study also identifies challenges such as student boredom when instructional strategies lack variation. The study concludes that Deuteronomy-based learning methods are effective in supporting character formation and positive behavioral development when applied consistently and creatively. These findings imply that Christian religious education can play a significant role in shaping student behavior when supported by professional teaching practices and collaboration between school and family.